Biochemical and Thermodynamical Characterization of Glucose Oxidase, Invertase, and Alkaline Phosphatase Secreted by Antarctic Yeasts - Yuivar, Yassef; Barahona, Salvador; Alcaíno, Jennifer; Cifuentes, Víctor; Baeza, Marcelo (Frontiers in Molecular Biosciences, 2017)
The use of enzymes in diverse industries has increased substantially over past decades, creating a well-established and growing global market. Currently, the use of enzymes that work better at ambient or lower temperatures in order to decrease the temperatures of production processes is desirable. There is thus a continuous search for enzymes in cold environments, especially from microbial sources, with amylases, proteases, lipases and, cellulases being the most studied. Other enzymes, such as glucose oxidase (GOD), invertase (Inv), and alkaline phosphatase (ALP), also have a high potential for application, but have been much less studied in microorganisms living in cold-environments. In this work, secretion of these three enzymes by Antarctic yeast species was analyzed, and five, three, and five species were found to produce extracellular GOD, Inv, and ALP, respectively. The major producers of GOD, Inv, and ALP were Goffeauzyma gastrica, Wickerhamomyces anomalus, and Dioszegia sp., respectively, from which the enzymes were purified and characterized. Contrary to expected, the temperatures at which the highest GOD and Inv activity were found were 64ºC and 60ºC, and 47ºC for ALP. However, enzymes maintain a significant percentage of activity at lower temperatures, especially the ALP that maintained a 67% and 43% of activity at 10ºC and 4ºC.